PENDAMPINGAN PEMBELAJARAN TATAP MUKA TERBATAS DALAM PEMBELAJARAN SEKOLAH DASAR PASCA PANDEMI COVID-19 - Mochamad Guntur; Riyanti Riyanti (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Learning during the transition from online learning to face-to-face learning is limited to making students lose their motivation to learn or learning loss. The aim of the quality pursuit program is to provide limited face-to-face learning assistance. The method used in the limited face-to-face mentoring process for this activity is a mix method with quantitative and qualitative analysis. In this activity program the samples used were SDN 3 Dukuhjati, SDN 3 Karangampel, and SDN 2 Tegalmulya and SDN 4 Srengseng. Elementary School Face-to-Face Learning Assistance Activities in 2021 starting from the activity preparation stage, implementation of activities and reporting carried out for 60 (sixty) calendar days calculated from the time the government aid funds were distributed. The results of this quality pursuit program are that students can improve learning outcomes, reduce learning loss that is affected by students and foster student learning motivation, and teachers are helped and can provide limited face-to-face assistance properly